DIGITAL MARKETING LANDSCAPE A COMPREHENSIVE SYSTEMATIC LITERATURE REVIEW - Januar Habibi Mahsyar; Micki Watulandi (INDONESIAN JOURNAL OF BUSINESS AND ECONOMICS, 2025)
This study presents a systematic literature review on digital marketing, aiming to synthesize existing research to identify key trends, gaps, and central issues in the field. The review comprehensively analyzes relevant academic articles published over the recent years, employing rigorous selection criteria and thematic categorization. Major findings highlight the growing importance of social media integration, artificial intelligence applications, and customer engagement strategies in digital marketing. However, challenges related to data privacy, measurement of digital marketing effectiveness, and alignment of traditional and digital marketing persist. The contributions of this review lie in providing a structured overview that aids researchers and practitioners in understanding evolving digital marketing dynamics and guiding future research directions.